2004
DOI: 10.1146/annurev.publhealth.25.101802.123046
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from Public Health Mass Media Campaigns: Marketing Health in a Crowded Media World

Abstract: Key Words health behavior, interventions, messages, counteradvertising, public service announcements s Abstract Every year, new public health mass media campaigns are launched attempting to change health behavior and improve health outcomes. These campaigns enter a crowded media environment filled with messages from competing sources. Public health practitioners have to capture not only the attention of the public amid such competition, but also motivate them to change health behaviors that are often entrenche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
322
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 517 publications
(348 citation statements)
references
References 45 publications
4
322
0
7
Order By: Relevance
“…It is also important to recognize that health promotion marketing campaigns exist in an environment that is competitive with, if not hostile to, their message (Randolph & Viswanth, 2004). Indeed, seniors rely on physicians and television for nutrition information, particularly if the seniors are of low income (Mckay, Houser, Blumberg, & Goldberg, 2006).…”
Section: Commercial Advertisingmentioning
confidence: 99%
“…It is also important to recognize that health promotion marketing campaigns exist in an environment that is competitive with, if not hostile to, their message (Randolph & Viswanth, 2004). Indeed, seniors rely on physicians and television for nutrition information, particularly if the seniors are of low income (Mckay, Houser, Blumberg, & Goldberg, 2006).…”
Section: Commercial Advertisingmentioning
confidence: 99%
“…Several studies have concluded that mass media is an effective way to influence the public's health behaviors by themselves or in addition to other programs (Abroms & Maibach, 2008;Bertrand et al, 2006;Noar, 2006;Randolph & Viswanath, 2004), although the effects are often modest (Noar, 2006). Successful health media campaigns have well-designed messages that are received by the target audience with effective reach and frequency (Abroms & Maibach, 2008, p. 221).…”
Section: Television and Mass Media Programs And Interventionsmentioning
confidence: 99%
“…Additionally, healthy campaigns often use medical jargon or focus on treatment rather than prevention. Despite these challenges, however, using mass media presents a positive opportunity for health promotion (Marshall-Chester, 1990) due to its wide reach, appeal, and costeffectiveness (Randolph & Viswanath, 2004). More research is needed to identify how the mass media can strategically influence health behavior practices (Abroms & Maibach, 2008).…”
Section: Television and Mass Media Programs And Interventionsmentioning
confidence: 99%
“…1063 These authors also suggest that accompanying campaigns with reinforcing "legislation and regulation" can influence the campaign impact and sustainability. An illustration of the impact of legislation and regulation can be seen in England and Wales where the national cleanyourhands campaign (Table IV.9.1) received considerable leverage with a parallel national target to reduce MRSA rates by 50%.…”
Section: National Campaigns Within Health Carementioning
confidence: 99%